A comprehensive review of integrating phase change materials in building bricks: Methods, performance and applications. (June 2023) - Gao, Yi; Meng, Xi
Abstract: The continuous growth of building energy consumption and carbon emissions has aggravated the balance between environment and energy, in which building heating and cooling accounts for the main part. Combining phase change materials (PCMs) with heat storage capacity with traditional bricks to form a building envelope can realize solar thermal utilization in buildings, weaken the influence of the outdoor environment on indoor temperature fluctuations, and achieve the purpose of energy saving. A detailed review has not been published to analyze the application of PCM in bricks. The purpose of this work is to provide a systematic review of PCM bricks, scrutinize the application of PCM bricks and identify current challenges and research prospects. Firstly, the application potential of PCM in buildings is briefly introduced. Secondly, the integration method of PCM in bricks and the heat transfer model of PCM bricks are described in detail. The influencing factors of PCM on the thermal performance of bricks are discussed, including outdoor conditions, PCM filling position, PCM heat transfer surfaces, PCM thermal properties, and PCM ventilation techniques. Finally, the experimental and numerical applications of PCM bricks in walls and buildings are analyzed in detail, including wall thermal performance, indoor thermal environment, energy consumption, and construction cost analysis. The main results and recommendations of the review showed that form-stabilization and macro-encapsulation are the two main integration methods for PCM bricks. There is a lack of high-precision numerical simulation methods for dealing with phase change heat transfer in the building field. The optimum melting temperature of the PCM depends on the climatic conditions. PCM bricks combined with ventilation systems or insulation materials are encouraged. Graphical abstract: Unlabelled Image Highlights: The performance improvement of filling PCMs into bricks have been evaluated. The suitable filling methods and locations were elaborated. The PCM contribution were evaluated on lowering energy consumption. Future directions were discussed on possible studies and applications.